The Olympic games, sports law and human rights - Mestre, Alexandre Miguel 1974- (Routledge, 2025)
"This book explores the relationship between sports law, the Olympic Movement and human rights. Examining the historical legal roots of contemporary 'Olympic law', including the ancient history of the Olympic Games and the legacy of Pierre de Coubertin, the book shines new light on one of the most important issues in world sport today. Offering a new inter-disciplinary perspective on Olympic law, drawing on legal theory, history and contemporary social scientific studies in sport, this book is fascinating reading for any advanced student, researcher, policy-maker or practitioner with an interest in sports law, the Olympic Games, mega-events or human rights"--
"Routledge Focus" -- from cover
Keywords: Olympics / Law and legislation; Sports / Law and legislation; Olympic games (Ancient) / Law and legislation; Olympics / Social aspect.s; Athletes / Legal status, laws, etc; Human rights; Freedom of expression; Coubertin, Pierre de / 1863-1937; Droits de l'homme (Droit international); Liberté d'expression